Enseñanza y aprendizaje de la Estadística Descriptiva en el nivel de educación secundaria - Gualán Jiménez, Josselyn Daniela (2024)
Statistics teaching and learning is a fundamental aspect to develop the analytical skills and the understanding of data in secondary school students. That is why this research seeks to investigate the methodological strategies for the teaching and learning of Descriptive Statistics. To do this, it was performed a rigorous process of systematic documentary review in articles, theses, reports and book chapters. The search for information was executed in scientific databases such as Dialnet, SciELO, Scopus and Eric; also, in searching engines such as Google academic, Bing among others. The search equations were entered in the Spanish, English and Portuguese languages: The selection and organization techniques were performed through search logs, bibliographic and content sheets. Out of all the documents collected, 31 were chosen under the criterion of concordance with the conceptual categories: difficulties in teaching and learning Descriptive Statistics, and didactic sequences for its teaching. As a result; 7 difficulties were identified, from which, the most common are the relation between the theoretical and the practical, and the representation and interpretation of results; The most used and most suggested sequence by different authors is the Project-Based Learning (PBL). Therefore, it is concluded that teaching Descriptive Statistics requires both disciplinary and pedagogical skills, this requires teachers to have a mastery of disciplinary content and teaching methods. Key words: Teaching and learning, statistics difficulties, didactic sequences, Project Based Learning.